2021
DOI: 10.1111/ijcp.14605
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to Pfizer‐BioNTech vaccination of healthcare workers at Malta's state hospital

Abstract: Background The long‐term control of COVID‐19 depends on an effective global vaccination strategy. Protecting healthcare workers (HCWs) from serious infection is critical. Malta, a European country, initiated the vaccination roll‐out using Pfizer‐BioNTech COVID‐19 vaccine targeting HCWs. This study determined vaccination adverse effects (AEs) in this cohort. Method An online survey was disseminated to all HCWs via work email (29/3/21 to 9/4/21) to gather AEs regarding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 20 publications
8
38
0
5
Order By: Relevance
“…To date, several independent (non-sponsored) phase IV studies on mRNA-based COVID-19 vaccines have been published from various countries, e.g., Czech Republic, Germany, Greece, Iraq, Italy, Jordan, Malta, Poland, Saudi Arabia, the UK, and the USA [13,[19][20][21][22][23][24][25][26][27][28][29][30]. The results of these phase IV studies generally agreed with the results of the phase III trials executed by the manufacturers and published by the regulators, i.e., the Centers for Disease Control and Prevention (CDC) [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several independent (non-sponsored) phase IV studies on mRNA-based COVID-19 vaccines have been published from various countries, e.g., Czech Republic, Germany, Greece, Iraq, Italy, Jordan, Malta, Poland, Saudi Arabia, the UK, and the USA [13,[19][20][21][22][23][24][25][26][27][28][29][30]. The results of these phase IV studies generally agreed with the results of the phase III trials executed by the manufacturers and published by the regulators, i.e., the Centers for Disease Control and Prevention (CDC) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Menni et al (2021) found that systemic side effects were significantly more common among the ≤55 years than the >55 years old recipients of BNT162b2 in the UK [20]. Cuschieri et al (2021) found that the BNT162b2 side effects reported by Maltese healthcare workers were significantly higher among those aged below 45 years old regardless of their sex [27]. Almufty et al (2021) found that the <50-year-old participants were prone to increased prevalence and intensity of post-vaccination side effects in Iraq [24].…”
Section: Discussionmentioning
confidence: 99%
“…The potential sex disparity in vaccine adverse events is not a new occurrence, according to findings related to other vaccines [ 24 , 25 ], due to a relative suppression of the cellular immune response of males compared to females [ 26 ]. These differences may be explained with important biological associations between sex and immune responses [ 27 ], and effects on disease susceptibility, transmission, and vaccination outcomes [ 28 ]. The major sex hormones seem to exhibit opposing effects on the adaptive and innate immune system, with elevated estradiol increasing and testosterone decreasing the vaccine-induced antibody responses [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major sex hormones seem to exhibit opposing effects on the adaptive and innate immune system, with elevated estradiol increasing and testosterone decreasing the vaccine-induced antibody responses [ 29 , 30 ]. Moreover, autoimmune disorders are more common reported in women than men [ 31 ], together with behavioral attitudes to report adverse events [ 27 ]. Females could be also more susceptible to adverse effects due to higher body fat content affecting both volume of distribution and drug clearance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also allowed to report no symptoms by leaving the box unchecked. We have included a subsection for side effects where we listed the most frequent side effects reported by other studies [20,[29][30][31][32], including pain at the sites of injection, fatigue, headache, fever and chills, nausea, and vomiting. Additionally, we also provided a section for reporting other unlisted side effects which might have been experienced by our study participants.…”
Section: Study Design Population and Settingmentioning
confidence: 99%